PENERAPAN MEDIA PEMBELAJARAN KAMUS PUTAR DEUTSCH-INDONESISCH DALAM KETERAMPILAN MENULIS KALIMAT DESKRIPTIF BAHASA JERMAN SISWA KELAS X MIA 6 SMAN 2 BANGKALAN - MUSYAROFAH, SITI (LATERNE, 2017)
Writing in a foreign language is most difficult when learning. Students at the SMAN 2 Bangkalan have difficulty finding the idea, especially in descriptive writing. Therefore, teachers as the central components in the learning process must be creative and innovative. In order to help the student, therefore, any learning media that is Kamus Putar Deutsch-Indonesisch applied. Media Kamus Putar selected, because when someone learns German, one always needs a dictionary. The location of the wording book is at first thick and the students are not interested in that. But this media presents a form of the dictionary that is more practical and not equal to the other in general dictionaries. In this essay, researcher take two main things as an object which are : “1) How to apply learning media using Kamus Putar Deutsch-Indonesisch to improve students skills in writing deceptive text.